Ultrasmall metal oxide nanocrystals embedded in nitrogen-doped carbon networks based on one-step pyrolysis of bi-functional metallo-organic molecules for high-performance lithium-ion batteries. (20th January 2020) - Li, Liuqing; Zhang, Haiyan; Cheng, Ao; Zhong, Weihao; Li, Zhaopeng; Li, Zhenghui
Abstract: Commercial phthalocyanine dyes, including tin phthalocyanine and iron phthalocyanine, are employed as precursors to fabricate SnO2 /Fe2 O3 nanocrystals embedded in carbon framework by simple one-step in-situ pyrolysis. Phthalocyanine dyes are typical metallo-organic molecules incorporating N-containing conjugated organic shell and single metal atom core (Sn or Fe here), which can serve as the resources of both N-doped porous carbon and SnO2 /Fe2 O3 nanocrystals. Meanwhile, electronegative N atoms combined with rigid conjugated organic ligands is helpful for restricting the aggregation of metal ions during carbonization, leading to the generation of ultrasmall SnO2 /Fe2 O3 nanocrystals embedded in amorphous carbon framework (denoted as SnO2 /N-PC and Fe2 O3 /N-PC). The obtained SnO2 /N-PC and Fe2 O3 /N-PC have stable carbon continuous phase, ultrasmall and well-distributed metal oxide nanocrystals and porous skeleton, and then display superior lithium storage performance. SnO2 /N-PC delivers high initial discharge and charge capacities of 1654 mAh g −1 and 1084 mAh g −1 ; after cycling for 200 times, it retains a reversible capacity of 775 mAh g −1, which is nearly 80% against the capacity of the second cycle. Fe2 O3 /N-PC presents high reversible capacity of 1123 mAh g −1 after 136 cycles at 200 mA g −1, and 612 mAh g −1 after 200 cycles at 1 A g −1 .